Rethinking school inclusion during and after the pandemic: some reflections - Ines Guerini; Mirca Montanari; Giorgia Ruzzante; Alessia Travaglini (Firenze University Press, 2021)
This contribution, of a theoretical nature, focuses on the complex educational situation that emerged immediately after the lockdown period and extended to this day. The authors, in fact, reflect on how the legislative restrictions, issued in favor of containing the spread of Covid-19, have significantly decreased the chances of building/maintaining significant relational bonds. This has consequently had a negative impact on the development of inclusive processes as well as on the learning level of many students, especially for the most vulnerable ones. For this reason, the authors try to question what prospects and what possibilities will open in the post-pandemic period, keeping in mind the unavoidable need to re-think the school, both from an organizational and an educational-didactic point of view.   Ripensare l'inclusione scolastica durante e dopo la pandemia: alcuni spunti di riflessione.   Il presente contributo, di carattere teorico, si focalizza sulla complessa situazione educativa delineatasi subito dopo il periodo del lockdown e prorogatasi finora. Le autrici, difatti, riflettono su come le restrizioni normative, emanate in favore della riduzione del contagio da Covid-19, abbiano sensibilmente diminuito le possibilità di costruire/mantenere legami relazionali significativi. Questo ha, conseguentemente, avuto un impatto negativo sullo sviluppo dei processi inclusivi nonché sul livello apprenditivo di numerosi alunni, soprattutto di quelli più vulnerabili. In ragione di ciò, le autrici provano a interrogarsi su quali prospettive e su quali possibilità si aprano nel periodo post-pandemia, avendo bene in mente l'ineludibile esigenza di ri-pensare la scuola, tanto dal punto di vista organizzativo quanto da quello educativo-didattico.